Parental Participation and Family Support on Student Learning Outcomes - Wibawati, Halida Novi; Haryanto, Sigit (Proceedings International Conference on Education Innovation and Social Science, 2025)
This study aims to analyze the influence of parental involvement and family support on students' academic achievement. The background of the research is rooted in the phenomenon of declining student performance, which is not solely caused by internal factors, but also by external influences, particularly from the family environment. The research employed a quantitative approach using a correlational survey method. The sample consisted of 11th-grade students and their parents at SMA Islam Al Azhar 7 Solobaru, selected through stratified random sampling. Data were collected using a Likert-scale questionnaire to measure the level of parental involvement, types of family support, and students' academic outcomes, which were assessed through report card scores. The statistical analysis revealed a significant and positive correlation between parental involvement and students' academic achievement (r = 0.642; p < 0.01), as well as between family support and academic achievement (r = 0.599; p < 0.01). Multiple linear regression analysis showed that both variables simultaneously contributed 51.2% to student academic outcomes. These findings indicate that higher levels of parental engagement and stronger family support positively influence student learning outcomes. The results suggest a need for strengthened collaboration between schools and families as a strategic effort to improve educational quality.